SOD1 Mutation Spectrum and Natural History of ALS Patients in a 15-Year Cohort in Southeastern China - Chen, Lu-Xi; Xu, Hai-Feng; Wang, Pei-Shan; Yang, Xin-Xia; Wu, Zhi-Ying; Li, Hong-Fu (Frontiers in Genetics, 2021)
Background: Mutations in superoxide dismutase 1 gene (SOD1) are the most frequent high penetrant genetic cause for amyotrophic lateral sclerosis (ALS) in the Chinese population. A detailed natural history of SOD1-mutated ALS patients will provide key information for ongoing genetic clinical trials. Methods: We screened for SOD1 mutations using whole exome sequencing (WES) in Chinese ALS cases from 2017 to 2021. Functional studies were then performed to confirm the pathogenicity of novel variants. In addition, we enrolled previously reported SOD1 mutations in our centers from 2007 to 2017. The SOD1 mutation spectrum, age at onset (AAO), diagnostic delay, and survival duration were analyzed. Results: We found two novel SOD1 variants (p.G17H and p.E134*) that exerted both gain-of-function and loss-of-function effects in vitro. Combined with our previous SOD1-mutated patients, 32 probands with 21 SOD1 mutations were included with the four most frequently occurring mutations of p.V48A, p.H47R, p.C112Y, and p.G148D. SOD1 mutations account for 58.9% of familial ALS (FALS) cases. The mean (SD) AAO was 46 ± 11.4 years with a significant difference between patients carrying mutations in exon 1 [n = 5, 34.6 (12.4) years] and exon 2 [n = 8, 51.4 (8.2) years] (p = 0.038). The mean of the diagnostic delay of FALS patients is significantly earlier than the sporadic ALS (SALS) patients [9.5 (4.8) vs. 20.3 (9.3) years, p = 0.0026]. In addition, male patients survived longer than female patients (40 vs. 16 months, p = 0.05). Conclusion: Our results expanded the spectrum of SOD1 mutations, highlighted the mutation distribution, and summarized the natural history of SOD1-mutated patients in southeastern China. Male patients were found to have better survival, and FALS patients received an earlier diagnosis. Our findings assist in providing a detailed clinical picture, which is important for ongoing genetic clinical trials.